Thioredoxin-1: A Promising Target for the Treatment of Allergic Diseases - Wang, Jinquan; Zhou, Jiedong; Wang, Cuixue; Fukunaga, Atsushi; Li, Shujing; Yodoi, Junji; Tian, Hai (Frontiers in Immunology, 2022)
Thioredoxin-1 (Trx1) is an important regulator of cellular redox homeostasis that comprises a redox-active dithiol. Trx1 is induced in response to various stress conditions, such as oxidative damage, infection or inflammation, metabolic dysfunction, irradiation, and chemical exposure. It has shown excellent anti-inflammatory and immunomodulatory effects in the treatment of various human inflammatory disorders in animal models. This review focused on the protective roles and mechanisms of Trx1 in allergic diseases, such as allergic asthma, contact dermatitis, food allergies, allergic rhinitis, and drug allergies. Trx1 plays an important role in allergic diseases through processes, such as antioxidation, inhibiting macrophage migration inhibitory factor (MIF), regulating Th1/Th2 immune balance, modulating allergic inflammatory cells, and suppressing complement activation. The regulatory mechanism of Trx1 differs from that of glucocorticoids that regulates the inflammatory reactions associated with immune response suppression. Furthermore, Trx1 exerts a beneficial effect on glucocorticoid resistance of allergic inflammation by inhibiting the production and internalization of MIF. Our results suggest that Trx1 has the potential for future success in translational research.